Psychological determinants of learning activities of academically underachieving university students - E. Yu. Cherniakevich (Вестник университета)
The article raises the problem of university students' academic failure. The results of an empirical study aimed at studying the features of the learning activity style, self-organisation processes, academic motivation, personal meaning of learning for academically unsuccessful students are presented. The study involved 32 students of the 2nd and 3rd courses of the technical university. Research methods: T.O. Gordeeva’s “Scale of academic motivation”, N.A. Kopeyna’s questionnaire “Style of learning activity”, A.D. Ishkov’s methodology “Diagnostics of self-organisation features (DOS)”, test of unfinished sentences “For me, my studies are ...”. The psychological determinants of students' academic failure have been revealed: amotivation dominance, study meaningfulness lack, low goal-setting level, low strong-willed efforts level, low planning skills' level, perception of study as an unpleasant necessity.